Agostinho de Hipona e Luigi Pareyson: uma análise comparativa sobre o problema do mal - MARQUES, Miqueas Protasio (2024)
The aim of this paper is to carry out a comparative analysis of the problem of evil in the thought of Augustine of Hippo and Luigi Pareyson. Augustine in De libre arbítrio (Free Will - 387-395), a work dedicated to the problem of evil, denies the idea of ontological evil, conceiving it as non-being, and positions the problem solely in the field of morality based on the notion of sin, which according to him has its origin in the free will of the human will; in this way, Augustine excludes God's responsibility for the existence of sin, even though he is its redeemer. Pareyson, on the other hand, in Ontology of Freedom: Evil and Suffering (1955), presents his vision of the negative through a hermeneutic of religious experience, giving evil an ontological status, which in addition to being a reality, that is, a positive reality in its negativity, affirms that God is the origin of evil and man its author. Both authors use the biblical narrative of “creation”, “fall” and “redemption” to reflect on the problem of evil. Therefore, in order to achieve this goal, we will analyze both the Augustinian view of evil from The Free Will, and Pareyson's hermeneutics in Ontology of Freedom: Evil and Suffering, and finally, we will compare their theories, identifying their approximations and diferences.